Evaluación de bioestimulantes aplicados al follaje de Lechuga “romana” (Lactuca sativa L.) en la zona de Babahoyo, provincia Los Ríos - TERÁN MORENO JOSE LUIS (2025)
Lettuce Lactuca sativa L. is one of the crops that is gaining more importance due to its fundamental role in the daily diet of modern consumers. It is particularly useful for the human body in terms of health, in particular, it is one of the great suppliers of vitamin K with a content of 113 μg in each 100 g serving and is considered a low-calorie vegetable, providing up to 19.6 kcal per 100 g. The purpose of this study is the effectiveness of biostimulants applied through the foliage of Roman lettuce Lactuca sativa L. in the Babahoyo area, Los Ríos. The present study was carried out at the experimental farm 'Jorge Yánez Castro' of the Faculty of Agricultural Sciences (FACIAG), Technical University of Babahoyo (UTB). “Roman” variety seeds were used for sowing. The experimental design applied was Randomized Complete Blocks, which included thirteen treatments and was carried out with three repetitions. To make comparisons and adjustments in the means of the investigated treatments, the Tukey test was used at a level of 95% reliability. The results of the study allowed us to affirm that the application of growth biostimulants in the crop serves as an increase in the growth and production of romaine lettuce in the town of Babahoyo. Specifically, the application of Newfol Plus in a dose of 350 g had greater production, yield, and net profit with a cost-benefit ratio of 2.22 with the other products in the study. Keywords: biostimulants; vegetables; production.